Risk factors for symptom recurrence after microwave ablation of adenomyosis: a preliminary retrospective study - Sainan Guan; Yongyan He; Xi Zhou; Jinxiu Wan; Haijing Peng; Guojuan Bu; Shuang Liang; Huahui Liu; Shiying Huang; Erjiao Xu (International Journal of Hyperthermia)
Introduction Microwave ablation (MWA) effectively treats adenomyosis, yet symptom recurrence remains challenging. Thus, our study aims to explore the independent risk factors related to symptom recurrence after MWA of symptomatic adenomyosis.Material and methods Patients with symptomatic adenomyosis who received MWA treatment at our institute from June 2020 to June 2023 were retrospectively included. Preoperative and intraoperative clinical data were retrospectively collected, and symptom relief following MWA was systematically monitored. Independent risk factors for symptom recurrence after MWA of adenomyosis were explored through Cox regression analysis. Kaplan-Meier (K-M) curves were plotted to estimate recurrence-free survival, and differences between groups were analyzed using the Log-Rank test.Result In total, 38 patients with adenomyosis were included, with a median follow-up duration of 15 months (interquartile range: 10-23 months). Among them, 81.58% (31/38) of patients experienced significant symptom relief, while 18.42% (7/38) reported partial relief, culminating in a clinical success rate of 100%. The symptom recurrence rate was 21.05% (8/38). Multivariate COX proportional hazards regression indicated that the fertility requirement, the absence of artificial ascites during the MWA procedure, and inadequate EPV (<524 J/cm3) were independent risk factors for symptom recurrence after MWA of adenomyosis.Conclusion MWA is an effective treatment for relieving symptoms of adenomyosis. While fertility requirements, without artificial ascites assistance, and lower EPV were independent risk factors for symptom recurrence after MWA of adenomyosis.